2022
DOI: 10.3389/fenvs.2022.1022046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of public–private partnership investment, financial development, and renewable energy consumption on the ecological footprint in South Asia and the Pacific region

Abstract: The improvement of environmental quality has become a major challenge for all countries. Against the strategic background of environmental protection, this study investigated the role of public–private partnership investment (PPPI) in energy and transport, financial development, and renewable energy on ecological footprint (EF) in South Asia and the Pacific region, utilizing the autoregressive distributive lag (ARDL) model spanning the time 1990–2017. The outcomes of the ARDL show that PPPI in energy and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…For example, Yang et al [33] showed that public-private partnership investment in energy led to carbon emissions in the context of emerging economies, specifically the E-7 countries (China, Turkey, Russia, India, Indonesia, Brazil, and Mexico). Other empirical studies with similar conclusions include Ahmad and Raza [7] regarding Brazil, Kirikkaleli and Adebayo [30] regarding India, Shahbaz et al [6] and Lu et al [32] regarding China, Caglar et al [31] regarding the BRICS panel, Chunling et al [34] regarding Pakistan's ecological footprint, and Wen et al [35] regarding the ecological footprint of the South Asia and Pacific regions.…”
Section: Literature Reviewmentioning
confidence: 81%
“…For example, Yang et al [33] showed that public-private partnership investment in energy led to carbon emissions in the context of emerging economies, specifically the E-7 countries (China, Turkey, Russia, India, Indonesia, Brazil, and Mexico). Other empirical studies with similar conclusions include Ahmad and Raza [7] regarding Brazil, Kirikkaleli and Adebayo [30] regarding India, Shahbaz et al [6] and Lu et al [32] regarding China, Caglar et al [31] regarding the BRICS panel, Chunling et al [34] regarding Pakistan's ecological footprint, and Wen et al [35] regarding the ecological footprint of the South Asia and Pacific regions.…”
Section: Literature Reviewmentioning
confidence: 81%
“…In our analysis, we focus on the selection of strategies that best meet the needs of sustainable development, while Cieślak engages in a more general review of the implementation and effectiveness of public-private partnerships using the case of Poland. A study by Wen et al (2022) assesses the impact of investments through public-private partnerships, financial development, and renewable energy consumption on environmental impact in South Asia and the Pacific. It shows the importance of built-in money strategies.…”
Section: Resultsmentioning
confidence: 99%